Second note on the genus Neacanista Gressitt, 1940 (Coleoptera: Cerambycidae: Lamiinae: Acanthocinini) - Huang, Gui-Qiang; Lin, Mei-Ying (Zootaxa, 2018)
Huang et al. (2015) treated Hoploranomimus Breuning, 1959 (type species: Acanthocinus harmandi Pic, 1939) and Paracanthocinus Breuning, 1965 (type species: Paracanthocinus laosensis Breuning, 1965) as junior synonyms of Neacanista Gressitt, 1940 (type species: Neacanista tuberculipenne Gressitt, 1940) and commented on the taxonomic status of Neacanista shirakii (Mitono, 1943).